Dosimetric end-to-end tests in a national audit of 3D conformal radiotherapy. (April 2018) - Lehmann, Joerg; Alves, Andrew; Dunn, Leon; Shaw, Maddison; Kenny, John; Keehan, Stephanie; Supple, Jeremy; Gibbons, Francis; Manktelow, Sophie; Oliver, Chris; Kron, Tomas; Williams, Ivan; et al.
Highlights: End-to-end radiotherapy audits have been performed on 94 occasions in Australia. Conformal fields were assessed on an anthropomorphic thorax phantom. Dose after lung measured low for analytical anisotropic algorithm (AAA) calculations. AAA also overestimated dose in tangential fields as used in breast cancer treatments. AAA underestimated dose to points inside lung inhomogeneities. Superposition and convolution algorithms had problems with large angle wedges. Abstract: Background and purpose: Independent dosimetry audits improve quality and safety of radiation therapy. This work reports on design and findings of a comprehensive 3D conformal radiotherapy (3D-CRT) Level III audit. Materials and methods: The audit was conducted as onsite audit using an anthropomorphic thorax phantom in an end-to-end test by the Australian Clinical Dosimetry Service (ACDS). Absolute dose point measurements were performed with Farmer-type ionization chambers. The audited treatment plans included open and half blocked fields, wedges and lung inhomogeneities. Audit results were determined as Pass Optimal Level (deviations within 3.3%), Pass Action Level (greater than 3.3% but within 5%) and Out of Tolerance (beyond 5%), as well as Reported Not Scored (RNS). The audit has been performed between July 2012 and January 2018 on 94 occasions, covering approximately 90% of all Australian facilities. Results: The audit pass rate was 87% (53% optimal). Fifty recommendations were given, mainly related to planning system commissioning. Dose overestimation behind low density inhomogeneities by the analytical anisotropic algorithm (AAA) was identified across facilities and found to extend to beam setups which resemble a typical breast cancer treatment beam placement. RNS measurements inside lung showed a variation in the opposite direction: AAA under-dosed a target beyond lung and over-dosed the lung upstream and downstream of the target. Results also highlighted shortcomings of some superposition and convolution algorithms in modelling large angle wedges. Conclusions: This audit showed that 3D-CRT dosimetry audits remain relevant and can identify fundamental global and local problems that also affect advanced treatments.